Paranoia: Michael Bennett #17 - Born, James O.; Patterson, James, 1947- (New York : Little, Brown and Company, 2025)
"NYPD Detective Michael Bennett will stop at nothing to protect family: his wife, his kid-and his fellow officers. At every death scene, Bennett says a prayer over the victim. But recently, too many of the departed have been fellow cops. "I want you to look at these deaths on special assignment," NYPD Inspector Celeste Cantor says. "Report only to me." Bennett excels as a solo investigator. But he's chasing a killer who feeds on isolation...and paranoia"--.
new book 2025 spring.
Keywords: Thrillers Suspense fiction; Crimes against; Bennett, Michael (Fictitious character); New York (N.Y.); Detective and mystery fiction; Serial murder investigation; Police; New York (State); Suspense fiction; Detective and mystery fiction; Thriller fiction; Detective fiction; Mystery fiction